Impact of type 2 diabetes and microvascular complications on mortality and cardiovascular outcomes in a multiethnic Asian population. Issue 1 (8th July 2021) - Yap, Jonathan; Anbalakan, Kamalesh; Tay, Wan Ting; Ting, Daniel; Cheung, Carol Yim; Sabanayagam, Charumathi; Cheng, Ching-Yu; Wong, Tien-Yin; Yeo, Khung Keong
Abstract : Introduction: Diabetes mellitus is a growing public health epidemic in Asia. We examined the impact of type 2 diabetes, glycemic control and microvascular complications on mortality and cardiovascular outcomes in a multiethnic population-based cohort of Asians without prior cardiovascular disease. Research design and methods: This was a prospective population-based cohort study in Singapore comprising participants from the three major Asian ethnic groups: Chinese, Malays and Indians, with baseline examination in 2004–2011. Participants with type 1 diabetes and those with cardiovascular disease at baseline were excluded. Type 2 diabetes, Hemoglobin A1c (HbA1c) levels and presence of microvascular complications (diabetic retinopathy and nephropathy) were defined at baseline. The primary outcome was all-cause mortality and major adverse cardiovascular events (MACEs), defined as a composite of cardiovascular mortality, myocardial infarction, stroke and revascularization, collected using a national registry. Results: A total of 8541 subjects were included, of which 1890 had type 2 diabetes at baseline. Subjects were followed for a median of 6.4 (IQR 4.8–8.8) years. Diabetes was a significant predictor of mortality (adjusted HR 1.74, 95% CI 1.45 to 2.08, p<0.001) and MACE (adjusted HR 1.64, 95% CI 1.39 to 1.93, p<0.001). In those with diabetes, higher HbA1c levels were associated with increased MACE rates (adjusted HR (per 1% increase) 1.18, 95% CI 1.11 to 1.26, p<0.001) but not mortality (p=0.115). Subjects with two microvascular complications had significantly higher mortality and MACE compared with those with only either microvascular complication (adjusted p<0.05) and no microvascular complication (adjusted p<0.05). Conclusion: Diabetes is a significant predictor of mortality and cardiovascular morbidity in Asian patients without prior cardiovascular disease. Among patients with type 2 diabetes, poorer glycemic control was associated with increased MACE but not mortality rates. Greater burden of microvascular complications identified a subset of patients with poorer outcomes.